Linguistic landscape and second language vocabulary acquisition: A sociolinguistic inquiry into student experiences - Bakr Bagash Mansour Ahmed Al-Sofi (Universitas Syiah Kuala, 2026)
Linguistic landscape (LL) can play a crucial role in language learning, including vocabulary acquisition. The present mixed-methods study addresses three key objectives: (a) investigating the extent to which the LL provides opportunities for incidental vocabulary acquisition among Saudi Science and Engineering Track (SSET) students, (b) identifying the students’ perceptions regarding the LL’s in developing vocabulary acquisition and vocabulary-based skills, and (c) determining the best strategies for retaining LL vocabulary. Data were collected in a two-phase process: initial photographic documentation by students, who gathered 476 signs from public and commercial spheres in the Saudi LL from various cities in the Saudi regions, including Bisha, Abha, Jazan, Jeddah, Riyadh, Al-Baha, Taif, Dammam, Al-Ula, Hafr Al-Batin, and Tabuk. Data were also collected through an online questionnaire administered to the same students to assess their perceptions regarding the LL’s role in enhancing their vocabulary acquisition. Content analysis and preliminary descriptive statistics were employed to analyze the collected data. The results revealed that the LL played a crucial role in enhancing various aspects of students’ vocabulary acquisition, and the participants held positive perceptions of its potential. Furthermore, several helpful strategies were identified for vocabulary retention. This foundational study highlights LL’s importance in the Saudi context, serving as a critical resource that stakeholders should integrate alongside traditional classroom materials to foster students’ language skills.